2007
DOI: 10.1039/b711620a
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline synthesis: scope and regiochemistry of photocyclisation of substituted benzylidenecyclopentanone O-alkyl and O-acetyloximes

Abstract: [DO NOT ALTER/DELETE THIS TEXT]Irradiation of substituted 2-benzylidenecyclopentanone O-alkyl and O-acetyloximes in methanol provides a convenient synthesis of alkyl, alkoxy, hydroxy, acetoxy, amino, dimethylamino and benzo substituted annulated quinolines. paraSubstituents yield 6-substituted-2,3-dihydro-1H-cyclopenta[b]quinolines with 8-substituted products being obtained from ortho-substituted starting materials. Reactions of meta-substituted precursors are highly regioselective, with alkyl substituents lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 81 publications
0
14
0
1
Order By: Relevance
“…[22] In analogous embodiments, the latter transformation has also been described as a "6π-electron cyclization" process. [23] In order to get insights into the participation of a radical mechanism, the reaction mixture containing 6a was treated with 2,6-di-tert-butyl-4-methylphenol (BHT, 10 mol-%). It was observed that the presence of this free radical inhibitor affected the production the isoquinoline from 72 % to 65 % yield, whereas access to the related 3,4-dihydroisoquinoline was more drastically reduced from 8 % to 2 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[22] In analogous embodiments, the latter transformation has also been described as a "6π-electron cyclization" process. [23] In order to get insights into the participation of a radical mechanism, the reaction mixture containing 6a was treated with 2,6-di-tert-butyl-4-methylphenol (BHT, 10 mol-%). It was observed that the presence of this free radical inhibitor affected the production the isoquinoline from 72 % to 65 % yield, whereas access to the related 3,4-dihydroisoquinoline was more drastically reduced from 8 % to 2 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the latter pathway, photochemically promoted stereochemical isomerization of oximes has been established (Scheme ) . Moreover, Pratt and co‐workers have reported that such processes can operate during electrocyclization reactions, although they did not identify a relationship between cyclization efficiency and oxime ether stereochemistry . This approach is especially attractive in the case of oxime ethers where the rate of thermal interconversion is extremely slow.…”
Section: Methodsmentioning
confidence: 99%
“…1 HNMR (400 MHz, CDCl 3 ): d = 7.74 (s, 1H), 7.14-7.05 (m, 3H), 7.00-6.96 (m, 3H), 3.89 (s, 3H), 3.81 (s, 3H), 1.31 (s, 12 H), 1.30 (s, 12 H); 13 CNMR (101 MHz, CDCl 3 ): d = 141. 0, 139.7, 138.8, 130.2 (2C), 128.8, 127.8 (2C), 126.3, 123.8, 84.3 (2C), 84.1 (2C), 62.0, 40.0, 24.9 ppm (8C), two quaternary missing due to quadrupolar relaxation; 11 Diborylalkene (2.50 g, 5.0 mmol) in o-DCB (50 mL) was stirred at 200 8Cf or 16 h. The reaction mixture cooled to room temperature and was filtered through silica gel. The residue was purified by flash column chromatography on silica gel to give 2e as ay ellow foam (1.60 g, 93 %).…”
Section: Methodsmentioning
confidence: 99%
“…In the course of our efforts to develop malaria mosquito-selective acetylcholinesterase inhibitors, 1 we required such compounds, which we term “Friedel-Crafts-restricted” tert -alkyl benzenes. Traditional strategies to prepare these compounds use “temporary” ortho - or para -hydroxy or amino groups to direct Friedel-Crafts 2 or other electrophilic aromatic substitution reactions; 3,4 subsequent removal of the temporary directing group then unveils the desired meta -substitution pattern. We sought a more direct route that would benefit from the large number of commercially available meta -substituted benzoic acids and acetophenones.…”
Section: Introductionmentioning
confidence: 99%